The Evolution of the Television Industry: an Oligopoly Facing Internet - Izquierdo-Castillo, Jessica (Historia y Comunicación Social, 2014)
Television in Spain is facing a time of uncertainty in the transition to the converged scenario. The structural analysis of this industry from a historical perspective can help identify key factors in the configuration of the sector. This paper presents an analysis of the evolution of the sector according to three main periods. Firstly, it approaches the privatization of the television in Spain and the development of a competitive sector. Secondly, it studies the increase in supply in the digital context. Finally, it focuses on the renewal process facilitated by the Internet and new forms of consumption of television content from the audience.